Analisis Pendapatan dan Kelayakan Usaha Home Industri Bolu Cukke di Kelurahan Jennae, Kabupaten Soppeng - Fitriani Fitriani; Mustari Mustari; Muhammad Dinar; Muh. Ihsan Said; Muhammad Hasan (Indonesian Journal of Social and Educational Studies, 2020)
This research is a quantitative descriptive study that aims to study and describe the income and profits of Bolu Cukke's business in Jennae Village, Liliriaja District, Soppeng Regency. The population in this study were all Bolu Cukke business owners in Jennae Village, Liliriaja Subdistrict, Soppeng District. The research conducted is to collect data that is related to the variables studied through library research and field research. Data collection techniques used were observation, interviews and documentation. The data testing techniques include revenue, revenue, R/C ratio analysis, and Break Event Point (BEP) analysis. The results showed that the Bolu Cukke Home Industry business in Jennae sub-district, Liliriaja sub-district, Soppeng district gained profits and deserves to be developed as income for the local community. This can be seen from the revenue ratio of Bolu Cukke business owners which is greater than the costs incurred during the period or production period.